Characterisation of an enhanced preclinical model of experimental MPO‐ANCA autoimmune vasculitis. Issue 2 (23rd July 2021) - Prendecki, Maria; Gulati, Kavita; Turner‐Stokes, Tabitha; Bhangal, Gurjeet; Chiappo, Derick; Woollard, Kevin; Cook, H Terence; Tam, Frederick WK; Roufosse, Candice; Pusey, Charles D; McAdoo, Stephen P
Abstract: Experimental autoimmune vasculitis (EAV) is a model of antineutrophil cytoplasm antibody (ANCA)‐associated vasculitis (AAV) induced by immunisation of susceptible rat strains with myeloperoxidase (MPO). Animals develop circulating MPO‐ANCA, pulmonary haemorrhage, and glomerulonephritis, although renal injury is mild and recovers spontaneously without treatment. In this study we aimed to augment the severity of glomerulonephritis. Following induction of EAV on day 0, a sub‐nephritogenic dose of nephrotoxic serum (NTS) containing heterologous antibodies to glomerular basement membrane was administered on day 14. This resulted in a significant increase in disease severity at day 28 compared to MPO immunisation alone – with more urinary abnormalities, infiltrating glomerular leucocytes, and crescent formation that progressed to glomerular and tubulointerstitial scarring by day 56, recapitulating important features of human disease. Importantly, the glomerulonephritis remained pauci‐immune, and was strictly dependent on the presence of autoimmunity to MPO, as there was no evidence of renal disease following administration of sub‐nephritogenic NTS alone or after immunisation with a control protein in place of MPO. Detailed phenotyping of glomerular leucocytes identified an early infiltrate of non‐classical monocytes following NTS administration that, in the presence of autoimmunity to MPO, may initiate the subsequent influx of classical monocytes which augment glomerular injury. We also showed that this model can be used to test novel therapeutics by using a small molecule kinase inhibitor (fostamatinib) that rapidly attenuated both glomerular and pulmonary injury over a 4‐day treatment period. We believe that this enhanced model of MPO‐AAV will prove useful for the study of glomerular leucocyte behaviour and novel therapeutics in AAV in the future. © 2021 The Authors. The Journal of Pathology published by John Wiley & Sons, Ltd. on behalf of The Pathological Society of Great Britain and Ireland.